Searching for flavor labels in food products: the influence of color-flavor congruence and association strength - Velasco, Carlos; Wan, Xiaoang; Knoeferle, Klemens; Zhou, Xi; Salgado-Montejo, Alejandro; Spence, Charles (Frontiers in Psychology, 2015)
Prior research provides robust support for the existence of a number of associations between colors and flavors. In the present study, we examined whether congruent (vs. incongruent) combinations of product packaging colors and flavor labels would facilitate visual search for products labelled with specific flavors in a Stroop-like manner. Across two experiments, a Stroop-like effect between flavor words and packaging colors is documented and we demonstrate that people are able to search for packaging flavor labels more rapidly when the color of the packaging is congruent with the flavor label (e.g., red/tomato) than when it is incongruent (e.g., yellow/tomato). In addition, when the packaging color was incongruent, those flavor labels that were more strongly associated with a specific color yielded slower reaction times and more errors (Stroop interference) than those that were less strongly tied to a specific color. Importantly, search efficiency was affected both by color/flavor congruence and association strength. Taken together, these results therefore highlight the role of color congruence and color-word association strength when it comes to searching for specific flavor labels.